Vitamin C suppresses cell death in MCF-7 human breast cancer cells induced by tamoxifen - Subramani, Tamilselvan; Yeap, Swee Keong; Ho, Wan Yang; Ho, Chai Ling; Omar, Abdul Rahman; Abdul Aziz, Suraini; Nik Abd. Rahman, Nik Mohd. Afizan; Mohamed Alitheen, Noorjahan Banu (Wiley-Blackwell Publishing, 2014)
Vitamin C is generally thought to enhance immunity and is widely taken as a supplement especially during cancer treatment. Tamoxifen (TAM) has both cytostatic and cytotoxic properties for breast cancer. TAM engaged mitochondrial oestrogen receptor beta in MCF-7 cells and induces apoptosis by activation of pro-caspase-8 followed by downstream events, including an increase in reactive oxygen species and the release of pro-apoptotic factors from the mitochondria. In addition to that, TAM binds with high affinity to the microsomal anti-oestrogen-binding site and inhibits cholesterol esterification at therapeutic doses. This study aimed to investigate the role of vitamin C in TAM-mediated apoptosis. Cells were loaded with vitamin C by exposure to dehydroascorbic acid, thereby circumventing in vitro artefacts associated with the poor transport and pro-oxidant effects of ascorbic acid. Pre-treatment with vitamin C caused a dose-dependent attenuation of cytotoxicity, as measured by acridine-orange/propidium iodide (AO/PI) and Annexin V assay after treatment with TAM. Vitamin C dose-dependently protected cancer cells against lipid peroxidation caused by TAM treatment. By real-time PCR analysis, an impressive increase in FasL and tumour necrosis factor-α (TNF-α) mRNA was detected after TAM treatment. In addition, a decrease in mitochondrial transmembrane potential was observed. These results support the hypothesis that vitamin C supplementation during cancer treatment may detrimentally affect therapeutic response.